Machine Learning–Based Prediction of Masked Hypertension Among Children With Chronic Kidney Disease. Issue 9 (7th July 2022) - Bae, Sunjae; Samuels, Joshua A.; Flynn, Joseph T.; Mitsnefes, Mark M.; Furth, Susan L.; Warady, Bradley A.; Ng, Derek K.; ,
Abstract : Background: Ambulatory blood pressure monitoring (ABPM) is routinely performed in children with chronic kidney disease to identify masked hypertension, a risk factor for accelerated chronic kidney disease progression. However, ABPM is burdensome, and developing an accurate prediction of masked hypertension may allow using ABPM selectively rather than routinely. Methods: To create a prediction model for masked hypertension using clinic blood pressure (BP) and other clinical characteristics, we analyzed 809 ABPM studies with nonhypertensive clinic BP among the participants of the Chronic Kidney Disease in Children study. Results: Masked hypertension was identified in 170 (21.0%) observations. We created prediction models for masked hypertension via gradient boosting, random forests, and logistic regression using 109 candidate predictors and evaluated its performance using bootstrap validation. The models showed C statistics from 0.660 (95% CI, 0.595–0.707) to 0.732 (95% CI, 0.695–0.786) and Brier scores from 0.148 (95% CI, 0.141–0.154) to 0.167 (95% CI, 0.152–0.183). Using the possible thresholds identified from this model, we stratified the dataset by clinic systolic/diastolic BP percentiles. The prevalence of masked hypertension was the lowest (4.8%) when clinic systolic/diastolic BP were both <20th percentile, and relatively low (9.0%) with clinic systolic BP<20th and diastolic BP<80th percentiles. Above these thresholds, the prevalence was higher with no discernable pattern. Conclusions: ABPM could be used selectively in those with low clinic BP, for example, systolic BP<20th and diastolic BP<80th percentiles, although careful assessment is warranted as masked hypertension was not completely absent even in this subgroup. Above these clinic BP levels, routine ABPM remains recommended.